Conditions of Visibility of Bridge Natural Frequency in Vehicle Vertical Acceleration. (2016) - Lalthlamuana, R.; Talukdar, S.
Abstract: For structural health monitoring, selected bridges are generally instrumented and recorded data are utilized to obtain the natural frequency. However, this method is expensive and cannot cover all the bridges. Hence an alternative way for finding the bridge natural frequency is to utilize the vertical acceleration of moving vehicle. In the present paper spectrogram of vehicle vertical acceleration obtained theoretically has been analyzed to determine the conditions for which fundamental or higher mode bridge frequencies are visible. A flexible vehicle model moving along a simply supported bridge has been analyzed. Effect of vehicle / bridge mass ratio and surface roughness conditions on the visibility of bridge natural frequency have been investigated.